Plasma Exosomal Proteomic Pattern of Epstein-Barr Virus-Associated Hemophagocytic Lymphohistiocytosis - Xie, Yan; Yang, Li; Cao, Pengfei; Li, Shen; Zhang, Wentao; Dang, Wei; Xin, Shuyu; Jiang, Mingjuan; Xin, Yujie; Li, Jing; Long, Sijing; Wang, Yiwei; et al. (Frontiers in Microbiology, 2022)
Abstract Epstein-Barr virus (EBV)-associated hemophagocytic lymphohistiocytosis (EBV-HLH) is a life-threatening syndrome caused by EBV infection that is usually refractory to treatment and shows relapse. Development of new biomarkers for the early diagnosis and clinical treatment of EBV-HLH is urgently needed. Exosomes have been shown to mediate various biological processes and are ideal noninvasive biomarkers. Here, we present the differential plasma exosomal proteome of a patient with EBV-HLH before vs. during treatment and with that of his healthy twin brother. A tandem mass tag (TMT)-labeled LC-MS technique was employed for proteomics detection. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses indicated that differential proteomic profiles were related to virus infection, coagulopathy, nervous system dysfunction, imbalance of immune response, and abnormal liver function. The candidate biomarkers were first identified in the patient’s plasma exosomes at different treatment and follow-up time points. Then, 14 additional EBV-HLH exosome samples were used to verify 6 differentially expressed proteins. The upregulation of C-reactive protein (CRP), moesin (MSN), galectin 3 binding protein (LGALS3BP), and heat shock cognate 71 kDa protein (HSPA8) and the downregulation of plasminogen (PLG) and fibronectin 1 (FN1) could serve as potential biomarkers of EBV-HLH. This plasma exosomal proteomics analysis provides new insights into diagnostic and therapeutic biomarkers of EBV-HLH.